More than a Title : Autoethnographic Explorations of Choosing Dissertation Topics in Applied Linguistics - Herrera, Luis Javier Pentón, (Educational Research E-Books Online, Collection 2025., 2025)
This edited book, the first of its kind in the field of applied linguistics, offers a refreshing and unique exploration of how personal experiences shape academic journeys. Through engaging autoethnographic inquiries, each chapter sheds light on the complex factors influencing doctoral students' decisions on dissertation topics. This collection provides deep insights into the interplay between identity, experience, and academic research, making it an essential read for anyone interested in the human aspects of applied linguistics. This book is a must-read for doctoral students, doctoral advisors, and anyone interested in doctoral studies, offering valuable perspectives on the how, what, and why of choosing dissertation topics in applied linguistics. Contributors are: Farah Ali, Anna Becker, Jaione Diaz Mazquiaran, Xuewei He, Ufuk Keleş, Akiko Kiyota, Justyna Legutko, Angel Merchant, Valéria Schörghofer-Queiroz, Marc Tamarit-Galdón, and Ethan Trinh.